Analisa Tax Planning Dengan Pemilihan Tarif Pajak Penghasilan (PPh) Badan PT Agp - Suci Tri Susilawati; Rumia Simanullang; Fajar Zakaria Hasanudin (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2022)
This research was conducted at PT AGP with the aim of finding out which use of the optimal income tax rates. The research method used in this research is descriptive qualitative research.The conclusion obtained from this study for the optimal calculation of the corporation's income tax for 2018-2019 for PT AGP is the tax non-tax incentive based on article 17 based on Law Number 36 Year 2018 regarding the Corporate Income Tax payable of 0.00- or nothing. Whereas if PT AGP during 2018-2019 used the tax rate compensation of the outstanding corporate income tax paid for the year 2018 yielded 10,489,428 and for 2019 the paid tax generated 31,705,366.00.PT AGP should study the applicable Taxation Law so that it can choose a more optimal corporate income tax rate. If PT AGP chooses non tax incentive rates or Article 17 tariffs according to Law Number 36 of 2008, the things that must be considered are Article 17 tarifs (Law Number 36 Year 2008) taking into account costs and certainly paying attention to fiscal corrections to costs in the Financial Statements other than Article 17 tarif (Law Number 36 Year 2008) can compensate for business losses to the following year.